1993
DOI: 10.1002/j.1550-8528.1993.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ‐Glutamyl Transpeptidase Levels and Hypertension in Non‐drinkers: A Possible Role of Fatty Liver in the Pathogenesis of Obesity Related Hypertension

Abstract: The relationships between increases in body mass index (BMI) and increases in hypertension were compared between non-drinkers with elevated serum gamma-glutamyl transpeptidase (gamma-GTP) levels (> or = 50 U/l) and those with normal levels, who comprised 10,952 men and 22,107 women aged 40-59 years recruited from an occupational health clinic. Hypertension was found in 16.1% and 13.5% of the men and women, and elevated serum g-GTP was found in 10.8% and 2.8% of the men and women, respectively. The prevalences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 9 publications
5
38
0
5
Order By: Relevance
“…Serum GGT is associated with hypertension, dyslipidemia, and abnormal glucose tolerance, suggesting that it is related to hepatic insulin resistance rather than non-alcoholic fatty liver disease (Ikai et al 1994;Nilssen and Førde 1994;Kang et al 2007). GGT plays a direct role in the generation of reactive oxygen species in the presence of iron or other transition metals (Brown et al 1998), inducing lipid peroxidation in human biological membranes (Paolicchi et al 1997), and is an indirect marker of antioxidant systems, with the primary function of maintaining the intracellular concentration of glutathione in response to oxidative stress (Karp et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Serum GGT is associated with hypertension, dyslipidemia, and abnormal glucose tolerance, suggesting that it is related to hepatic insulin resistance rather than non-alcoholic fatty liver disease (Ikai et al 1994;Nilssen and Førde 1994;Kang et al 2007). GGT plays a direct role in the generation of reactive oxygen species in the presence of iron or other transition metals (Brown et al 1998), inducing lipid peroxidation in human biological membranes (Paolicchi et al 1997), and is an indirect marker of antioxidant systems, with the primary function of maintaining the intracellular concentration of glutathione in response to oxidative stress (Karp et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, several epidemiological studies have highlighted the particular association of raised g-glutamyl transferase (gGT) and hypertension. [19][20][21][22][23][24][25] A recent prospective study has confirmed a positive association between age, serum gGT and the subsequent risk of hypertension. 26 This relationship between gGT and hypertension may be independent of alcohol consumption, where gGT has been shown to correlate with systolic and diastolic blood pressure (Table 3).…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%
“…39 -44 The connection between GGT and the metabolic syndrome extends to an association of higher GGT levels with hypertension. [45][46][47][48][49] Thus, it appears that all of the major components of the metabolic syndrome are linked to elevations of serum GGT.…”
mentioning
confidence: 99%